(untitled) (Journal of the College of Basic Education, 2022)
The film derives from movement all its peculiarities and travels through it to a world full of movement and life. However, movement has two aspects, the first is physical, represented by moving and spatial transformation, and contributes to revitalizing the thing, and another adds to all this a sense of the movement having added capabilities at the level of significance and meaning, and at that time movement can be described. It possesses a special movement, so the concept of movement rises with imaginary sensory connotations that are not associated with physical movement, but rather it is a tool for understanding the activity of ideas carried by the thing. Alfilmi) aims to identify the movement and what its representations and requirements are in the filmic text, and this is represented in the research problem